RECOVERY OF CORRUPTION ASSET - SH, Mawardi (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
Asset recovery implementation that perform by prosecutor based on Article 18 letter b Law Number 31 Year 1999 on Corruption Eradication juncto Law Number 20 Year 2001 on Amendment Law Number 31 Year 1999 on Corruption Eradication. Whether there is any loss from corruption, it will rise obligation toward the convict to restitute amount of money as the consequence of their action. To restitute the money, it can be done by confiscation or auction the corruption result by the convict equal to the loss. Attorney General can perform the execution for asset recovery to accomplish corruption case. Key Word : Recovery, Corruption Asset, Criminal law